Educação musical: a importância do aprendizado musical a partir dos preceitos inacianos - Sens, Juliana (Universidade do Vale do Rio dos Sinos, 2023)
This article aims to revisit the concepts of Jesuit education through Ignatian Pedagogy, and converges to music education as a way to practice all the concepts involved in music, from the individual's immersion in different musical cultures to the multi-disciplinarity that music can contribute. Music makes the individual more socialized and also sharpens their creativity when that individual is involved musically. Through a field experience conducted in the classroom, with the fifth-grade classes of Colégio Catarinense, located in Florianópolis/SC, it is possible to see how music prepares students from elementary school for a culturally critical being, in addition to counting on the interaction between disciplines and the participation of students and teachers. This works brings theoretical background of authors such as: Penna (2008), França; Swanwick (2002), Beineke (2008) and Brito (2003), who affirm the importance of Music Education for the integral formation of the subject.
Keywords: Musicalização; Formação integral; Rede jesuíta; Musicalization; Integral formation; Jesuit network